Preparation of Electrosprayed, Microporous Particle Filled Layers - Venkataraman, Mohanapriya; Yang, Kai; Xiong, Xiaoman; Militky, Jiri; Kremenakova, Dana; Zhu, Guocheng; Yao, Juming; Wang, Yan; Zhang, Guoqing (Polymers, 2020)
Polytetrafluoroethylene (PTFE) is a synthetic fluoropolymer known for its excellent hydrophobic properties. In this work, samples from PTFE dispersions with different combinations of water and carbon microparticles were prepared using an electrospraying method. The morphologies and sizes of carbon particles were investigated and the properties of layers including roughness, hydrophobicity and electrical resistivity were investigated. The non-conductive carbon microparticles were selected as a model particle to check the compatibility and electrospraying ability, and it had no effect on the hydrophobic and electrical properties. Carbon microparticles in polymer solution increased the degree of ionization and was found to be beneficial for the shape control of materials. The results showed that PTFE dispersion with the composition of water and carbon microparticles produced fine sphere particles and the layer fabricated with increased roughness. It was also found that the electrical resistivity and hydrophobicity of all the layers comparatively increased. The fabricated microporous layers can be used in various applications like interlining layer in multilayer textile sandwiches.
Keywords: PTFE; electrospraying; contact angle; electrical resistivity; hydrophobic; microporous